2009
DOI: 10.1177/039463200902200218
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Anti-TNF Agents in the Elderly

Abstract: Rheumatoid arthritis, ankylosing spondylitis and psoriatic arthritis are commonly thought of as inflammatory diseases that affect younger individuals. Although the initial presentation of these diseases is common in a patient's twenties or thirties, they usually persist for the duration of the patient's life. In addition, up to one-third of patients with RA have disease onset after 60 years of age. Anti-TNF-a therapies now have well-recognized safety profiles that have been demonstrated in the usual clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 27 publications
(23 reference statements)
1
26
1
Order By: Relevance
“…In contrast, the package inserts for IFX and UST both report no overall difference in safety in the geriatric population. While some studies have found no significant differences in AE in the elderly, other observational studies on rheumatoid diseases have revealed a significantly higher number of AE in the elderly compared with younger groups . Our study focused on patients aged 75 years or above, a group considered at higher risk than younger patients.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, the package inserts for IFX and UST both report no overall difference in safety in the geriatric population. While some studies have found no significant differences in AE in the elderly, other observational studies on rheumatoid diseases have revealed a significantly higher number of AE in the elderly compared with younger groups . Our study focused on patients aged 75 years or above, a group considered at higher risk than younger patients.…”
Section: Discussionmentioning
confidence: 94%
“…Only few studies have been published on this topic [18], while the use of biological agents in elderly patients with rheumatoid arthritis has been reported in a greater number of publications including a systematic review [19,20]. This latter review showed that elderly rheumatoid arthritis patients undergoing anti-TNF treatments have a higher number of adverse events and similar efficacy when compared with younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, tuberculosis reactivation with anti-TNF-a therapy seems to be higher in the elderly, especially in RA over the age of 60 years. The safety profile of anti-TNF-a agents in late-onset SpA has been previously discussed [61][62][63][64][65][66][67][68][69][70] and the conclusions were mixed, with no increased risk [61,62] or a higher risk of infection for these patients [63,64]. Biological agents other than anti-TNF-a agents (abatacept, rituximab, anakinra, tocilizumab) are ineffective in AS and SpA and thus are not discussed in the management of patients with late-onset SpA.…”
Section: Biological Agents and Innovative Drugs In Lateonset Spamentioning
confidence: 99%